Case Report: Electroanatomic mapping as an early diagnostic tool in arrhythmogenic cardiomyopathy - de Melo, Jose F.; Shabtaie, Samuel A.; van Zyl, Martin; Collins, Jeremy D.; Siontis, Konstantinos C. (Frontiers in Cardiovascular Medicine, 2024)
Background Abnormal substrate on invasive electroanatomic mapping (EAM) correlates with areas of myocardial thinning and fibrofatty replacement in Arrhythmogenic Cardiomyopathy (ACM). However, EAM parameters are absent from all sets of diagnostic criteria for ACM. Case summary A 41-year-old female with no significant family history was referred for evaluation of frequent premature ventricular complexes (PVCs). Twelve-lead ECG showed diffuse low-voltage QRS complexes. Holter monitor showed 28% burden of PVCs with various morphologies consistent with right ventricular (RV) inflow and outflow tract exits. Transthoracic echocardiogram revealed normal biventricular function and dimension. Cardiac magnetic resonance revealed a mildly increased indexed RV end-diastolic volume with normal RV systolic function and no dyssynchrony, akinesia, dyskinesia, or late gadolinium enhancement. Electrophysiologic study demonstrated 2 predominant PVC morphologies that were targeted with ablation, in addition to extensive abnormality with low-voltage and fractionated electrograms in the peri-tricuspid and right ventricular outflow tract free wall regions with septal sparing, suggestive of RV cardiomyopathy. Subsequent genetic testing revealed two pathogenic variants in the desmoplakin and plakophilin-2 genes, confirming the diagnosis of ACM. Conclusion Advanced RV electropathy can precede RV structural changes in ACM. Invasive evaluation of the electroanatomic substrate should be considered in select cases even when imaging findings are not diagnostic. Future iterations of ACM guidelines may need to consider EAM substrate as one of the diagnostic criteria. A high index of diagnostic suspicion for ACM should be maintained in patients with multifocal RV ectopy.